ANALYSIS OF THE CHARACTERISTICS OF AUTOMOTIVE MASS AIR FLOW SENSORS: ANALYSIS OF THE CHARACTERISTICS OF AUTOMOTIVE MASS AIR FLOW SENSORS - Trifonov, Tihomir; Hadjiivanov, Hristo (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
An analysis of the characteristics of automotive mass air flow sensors is made. A test system has been developed to study the sensors. The measurement data is processed with MATLAB using curve fitting.